Ongoing Moral Formation Of Priests - Ajiki, Pius T. T. (Advances in Social Sciences Research Journal, 2019)
A generation has now elapsed after the Second Vatican Council, but for most priests ordained before or during the Council, the great surprise of John XIII awakened a sense of anticipation and hope unprecedented during their lifetimes. Bishops also feel the excitement as they reclaimed their ancient identity as members of the college of Bishops (Cozzens 129). This new identity for the priests buoyed up the church and challenged it to bring the Gospel to the crossroads and networks of the global village. The Post Conciliar Church has called for a different way of being a priest, as we witness today. One of the ways the ministry of the priest has changed is obviously the authority crisis as exemplified in the current Ahiara Diocesan Clergies’ rejection of their Bishop, Most Reverend Peter EbereOkpaLeke. This paper discusses the Ongoing Moral Formation of Priests, and recommends that for effective ministry of the priesthood, there is need to enter into crisis like many world leaders have and came out leaving behind examples for the future generations. Moses entered into crisis and led the Israelites out of slavery. So also Gandhi in India, Martin Luther King Jr. and in our time, Nelson Mandela of South Africa came out leading his people to freedom. Nigeria priests and the Catholic Church is in crisis. Emmanuel, God who is with us, Christ Jesus, should lead us to be ambassadors of reconciliation in his Church.